Borate radical substituted and modified ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

By replacing the phosphate group in the positive electrode material of sodium ferric pyrophosphate, the problem of poor electron conductivity is solved, the specific capacity and cycle stability are improved, and the performance of more efficient sodium ion battery is achieved.

CN119400840APending Publication Date: 2025-02-07WUHAN UNIV

Patent Information

Application Number
CN202411692168.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The electron conductivity of existing sodium ferric pyrophosphate positive electrode materials makes it difficult to reach the theoretical value of their actual capacity, and designing methods to improve the electron conductivity is challenging.

Method used

Borate replaces some of the phosphate groups in sodium ferric pyrophosphate, occupy anionic sites, stabilizes the 3D framework, promotes diffusion and transport of sodium ions, and improves electron conductivity.

Benefits of technology

The specific capacity and electronic conductivity of the positive electrode material of sodium ferric pyrophosphate are improved, the problem of poor electronic conductivity is solved, and the cyclic stability and rate performance of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400840A_ABST
    Figure CN119400840A_ABST
Patent Text Reader

Abstract

The invention discloses a boric acid radical substituted and modified ferric sodium pyrophosphate positive electrode material as well as a preparation method and application thereof, and belongs to the field of sodium ion batteries. The method comprises the following steps: S1, adding a boron source into an aqueous solution of ferric sodium pyrophosphate, uniformly mixing to obtain a first solution, and drying to obtain xerogel; and S2, under the protection of inert gas, roasting the xerogel so as to replace part of phosphate radicals with boric acid radicals, thereby obtaining the boric acid radical substituted modified ferric sodium pyrophosphate positive electrode material. Part of phosphate radical groups in sodium ferric phosphate pyrophosphate are replaced with borate radicals, the ion diffusion rate can be increased, the electronic conductivity of the sodium ferric phosphate pyrophosphate positive electrode material is improved, meanwhile, the specific capacity of sodium ferric phosphate pyrophosphate is improved, and the problem that in the prior art, the related sodium ferric phosphate pyrophosphate positive electrode material is poor in electronic conductivity is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a borate-substituted modified sodium iron phosphate pyrophosphate positive electrode material, and a preparation method and application thereof. Background Art

[0002] Electrochemical energy storage technology has the advantages of high energy density, fast response speed and low environmental impact, and has always been the research focus of large-scale energy storage systems. Among them, sodium-ion batteries have been widely studied due to their abundant sodium reserves, low cost, and similar physical and chemical properties to lithium. Positive electrode materials play a vital role in sodium-ion battery systems, determining the energy density of the system. At present, the positive electrode materials of sodium-ion batteries mainly include layered oxides, Prussian blue and polyanion materials. Among them, polyanion compounds have the characteristics of stable three-dimensional framework, significantly long cycle life and excellent rate performance, which are conducive to the application research of large-scale energy storage systems.

[0003] The most common positive electrode materials for polyanionic compounds include phosphates, pyrophosphates and mixed phosphates. Among them, although olivine-type sodium iron phosphate (NaFePO4) is electrochemically active, it cannot be synthesized by conventional methods, which increases the difficulty and cost of preparation. Although sodium iron phosphate ore-type NaFePO4 is easy to synthesize, it is not electrochemically active. Sodium iron pyrophosphate (Na2FeP2O7) has a low theoretical specific capacity due to its large molecular weight, which limits its application. Therefore, a mixed sodium iron phosphate pyrophosphate Na4Fe3(PO4)2P2O7 that combines the advantages of the above two iron-based positive electrode materials has attracted the attention of researchers.

[0004] Na4Fe3(PO4)2P2O7 is considered to be a promising cathode material for sodium-ion batteries due to its NASICON-type three-dimensional framework, small volume change, and high theoretical specific capacity (129 mAh / g). However, the poor electronic conductivity of Na4Fe3(PO4)2P2O7 makes it difficult for its actual capacity to reach the theoretical value. Currently, it is still challenging to design methods to improve the electronic conductivity of sodium iron pyrophosphate cathode materials. Summary of the invention

[0005] In view of the deficiencies of the above prior art, one of the objects of the present invention is to provide a method for preparing a borate-substituted modified sodium iron pyrophosphate positive electrode material. By replacing part of the phosphate groups in the sodium iron pyrophosphate with borate, the ion diffusion rate can be accelerated, the electronic conductivity of the sodium iron pyrophosphate positive electrode material can be improved, and the specific capacity of the sodium iron pyrophosphate can be improved, thereby solving the problem of poor electronic conductivity of the related sodium iron pyrophosphate positive electrode material in the technology.

[0006] The above object of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a borate-substituted modified sodium iron pyrophosphate positive electrode material comprises the following steps:

[0008] S1. A boron source is added to an aqueous solution of sodium iron pyrophosphate, mixed evenly to obtain a first solution, and dried to obtain a dry gel;

[0009] S2. Under the protection of an inert gas, the dry gel is calcined to replace part of the phosphate with borate to obtain a borate-substituted modified sodium iron pyrophosphate positive electrode material.

[0010] The present invention replaces part of the phosphate groups in sodium iron pyrophosphate with borate groups, occupies anion sites, does not change the lattice structure, stabilizes the 3D framework and facilitates the diffusion and transmission of sodium ions, and prevents structural distortion and internal stress during charge and discharge. By replacing the phosphate groups with lighter borate anion groups, it is beneficial to improve the specific capacity of sodium iron pyrophosphate. The borate anion, according to the boron-oxygen coordination, will introduce point defect vacancies after successfully replacing the phosphate, which can accelerate the ion diffusion rate and improve the electronic conductivity of the sodium iron pyrophosphate positive electrode material.

[0011] Preferably, the molar ratio of the sodium ferric pyrophosphate to the boron source is 1:(0.05-0.15). More preferably, the molar ratio of the sodium ferric pyrophosphate to the boron source is 1:(0.05-0.1).

[0012] Preferably, the boron source includes at least one of boric acid, sodium borate and calcium borate.

[0013] Preferably, the calcination temperature is 500-550° C. and the calcination time is 6-10 hours.

[0014] Preferably, before calcining the dry gel, the method further comprises: pre-calcining the dry gel under the protection of an inert gas, wherein the pre-calcining temperature is 300 to 400° C. and the time is 2 to 4 hours.

[0015] Preferably, the preparation method of the aqueous solution of sodium ferric phosphate pyrophosphate is as follows: dissolve polyvinyl pyrrolidone, an iron source and a carbon source in water, stir evenly to obtain a second solution; add a phosphorus source and a sodium source to the second solution, stir evenly to obtain the aqueous solution of sodium ferric phosphate pyrophosphate.

[0016] Preferably, the molar ratio of the iron source to the carbon source is 1:(3-4.5); the molar ratio of the sodium source to the phosphorus source is 1:(0.8-1); and the molar ratio of the iron source to the phosphorus source is 3:(3.8-3.95).

[0017] Preferably, the iron source includes at least one of ferrous sulfate heptahydrate, ferric nitrate nonahydrate, and ferrous oxalate; the carbon source includes at least one of citric acid, oxalic acid, and glucose; the phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and sodium dihydrogen phosphate dihydrate; the sodium source includes at least one of sodium dihydrogen phosphate dihydrate, sodium acetate, sodium carbonate, and sodium nitrate.

[0018] Another object of the present invention is to provide a borate-substituted modified sodium iron pyrophosphate positive electrode material prepared by the preparation method.

[0019] Another object of the present invention is to provide an application of the borate-substituted modified sodium iron pyrophosphate positive electrode material in a sodium ion battery.

[0020] Compared with the prior art, the present invention is beneficial in that:

[0021] The present invention replaces part of the phosphate groups in sodium iron pyrophosphate with borate groups, occupies anion sites, does not change the lattice structure, stabilizes the 3D framework and facilitates the diffusion and transmission of sodium ions, and prevents structural distortion and internal stress during charge and discharge. By replacing the phosphate groups with lighter borate anion groups, it is beneficial to improve the specific capacity of sodium iron pyrophosphate. The borate anion, according to the boron-oxygen coordination, will introduce point defect vacancies after successfully replacing the phosphate, which can accelerate the ion diffusion rate and improve the electronic conductivity of the sodium iron pyrophosphate positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Na4Fe3(PO4) prepared in Example 1 1.9 (BO3) 0.1 (P2O7) XRD pattern of positive electrode material;

[0023] Figure 2 Na4Fe3(PO4) prepared in Example 1 1.9 (BO3) 0.1 (P2O7) SEM image of the positive electrode material;

[0024] Figure 3 This is the SEM image of the Na4Fe3(PO4)2(P2O7) cathode material prepared in Comparative Example 1;

[0025] Figure 4 Na4Fe3(PO4) prepared in Example 1 1.9 (BO3) 0.1 (P2O7) The charge and discharge curves of the first three cycles of charge and discharge of the positive electrode material;

[0026] Figure 5 Na4Fe3(PO4) prepared in Example 11.9 (BO3) 0.1 (P2O7) Cyclic performance diagram of positive electrode material at a current density of 0.2A / g;

[0027] Figure 6 Na4Fe3(PO4) prepared in Example 2 1.95 (BO3) 0.05 (P2O7) Cyclic performance diagram of positive electrode material at a current density of 0.2A / g;

[0028] Figure 7 Na4Fe3(PO4) prepared in Example 3 1.85 (BO3) 0.15 (P2O7) Cyclic performance diagram of positive electrode material at a current density of 0.2A / g;

[0029] Figure 8 This is a cycle performance diagram of the Na4Fe3(PO4)2(P2O7) positive electrode material prepared in Comparative Example 1 at a current density of 0.2A / g;

[0030] Fig. 9 Na4Fe3(PO4) prepared in Example 1 1.9 (BO3) 0.1 (P2O7) positive electrode material, Na4Fe3(PO4) prepared in Example 2 1.95 (BO3) 0.05 (P2O7) positive electrode material, Na4Fe3(PO4) prepared in Example 3 1.85 (BO3) 0.15 Rate diagram of Na4Fe3(PO4)2(P2O7) positive electrode material and Na4Fe3(PO4)2(P2O7) positive electrode material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0031] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The embodiment of the present invention provides a method for preparing a borate-substituted sodium iron pyrophosphate positive electrode material, comprising the following steps:

[0033] S1. A boron source was added to an aqueous solution of sodium iron pyrophosphate, mixed evenly to obtain a clear first solution, and dried to obtain a xerogel;

[0034] S2. Under the protection of an inert gas, the dry gel is pre-baked and then calcined to replace part of the phosphate with borate to obtain a borate-substituted modified sodium iron pyrophosphate positive electrode material.

[0035] In step S1, there are a variety of boron source materials to choose from, and the specific one to be used can be determined according to the actual preparation needs. For example, as an example, the boron source can be one or more of boric acid, sodium borate and calcium borate. The amount of sodium ferric pyrophosphate and the boron source can be determined according to the actual preparation needs. For example, as an example, the molar ratio of sodium ferric pyrophosphate to the boron source is 1: (0.05-0.2); preferably, the molar ratio of sodium ferric pyrophosphate to the boron source is 1: 0.1.

[0036] In step S1, the drying conditions can be determined according to actual preparation needs. For example, as an example, the drying temperature is 140-180° C. and the drying time is 8-10 hours.

[0037] In step S2, the pre-baking and calcining conditions can be determined according to the actual preparation needs. For example, as an example, the pre-baking temperature is 300-400°C and the time is 2-4 hours; the calcining temperature is 500-550°C and the calcining time is 6-10 hours. There are many materials for inert gas to choose from, and which one to use can be determined according to the actual preparation needs. For example, as an example, the inert gas is argon or nitrogen.

[0038] In step S1, the sodium ferric pyrophosphate phosphate can be directly used as a finished product or can be homemade. When homemade sodium ferric pyrophosphate phosphate is used, the preparation method of sodium ferric pyrophosphate phosphate includes the following steps:

[0039] P1. Dissolve PVP, iron source and carbon source in water and stir to obtain a clear second solution;

[0040] P2. Add a phosphorus source and a sodium source to the second solution, heat and stir, and obtain a clear, light green aqueous solution of sodium ferric pyrophosphate.

[0041] In step P1, the iron source has a variety of materials to choose from, and the specific one to be used can be determined according to actual preparation needs. For example, as an example, the iron source can be one or more of ferrous sulfate heptahydrate, ferrous nitrate nonahydrate and ferrous oxalate.

[0042] There are many materials available for the carbon source, and the specific one to be used can be determined according to actual preparation needs. For example, as an example, the carbon source can be one or more of citric acid, oxalic acid and glucose.

[0043] The amounts of the iron source and the carbon source can be determined according to actual preparation requirements. For example, as an example, the molar ratio of the iron source to the carbon source is 1:(3-4.5); preferably, the molar ratio of the iron source to the carbon source is 1:3.5.

[0044] In step P1, a carbon source is introduced as a complexing agent to complex with iron ions; at the same time, since polyvinyl pyrrolidone contains nitrogen element N, nitrogen-doped carbon can be coated on the surface of sodium ferric pyrophosphate in the subsequent pre-calcination and calcination processes. The nitrogen-doped carbon coating triggers the formation of external defects and active sites in the nitrogen-doped amorphous carbon layer, thereby providing more active sites, accelerating the reaction rate, increasing the conductivity of electrons / ions, and greatly improving the conductivity and diffusion rate of sodium ions.

[0045] In step P2, the phosphorus source has a variety of materials to choose from, and the specific one to be used can be determined according to actual preparation needs. For example, as an example, the phosphorus source can be one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and sodium dihydrogen phosphate;

[0046] There are a variety of materials available for the sodium source, and the specific one to be used can be determined according to actual preparation needs. For example, as an example, the sodium source can be one or more of sodium dihydrogen phosphate dihydrate, sodium acetate, sodium carbonate and sodium nitrate;

[0047] The amount of the sodium source and the phosphorus source can be determined according to actual preparation needs. For example, as an example, the molar ratio of the sodium source to the phosphorus source is 4:(3.8-3.95); preferably, the molar ratio of the sodium source to the phosphorus source is 4:3.9;

[0048] The molar ratio of the iron source to the phosphorus source is 3:(3.8-3.95).

[0049] Example 1

[0050] This embodiment provides a method for preparing a borate-substituted sodium iron pyrophosphate positive electrode material, comprising the following steps:

[0051] S1. Dissolve 0.3 g of polyvinyl pyrrolidone in 20 mL of deionized water and stir at room temperature for 30-50 min to obtain a clear solution. Weigh 0.834 g of ferrous sulfate heptahydrate and add it to the above solution, then weigh 0.736 g of citric acid and add it to the above solution. Stir continuously with a magnetic stirrer for 10 min to obtain a light green clear solution.

[0052] S2. 0.447 g of ammonium dihydrogen phosphate and 0.544 g of sodium acetate trihydrate were added to the above solution in sequence, and the solution was stirred continuously with a magnetic stirrer for 10 to 20 min to obtain a clear light green aqueous solution of sodium iron phosphate pyrophosphate;

[0053] S3. Add 0.0062 g of boric acid to the above solution and stir continuously with a magnetic stirrer for 10 to 30 min to obtain a clear solution;

[0054] S4. The above solution was transferred to an ultrasonic machine for ultrasonic treatment to fully and evenly mix to form an emerald green transparent solution;

[0055] S5. The emerald green transparent solution was transferred to a drying oven and dried at 160°C for 10 h to obtain a black xerogel;

[0056] S6. The obtained black dry gel was ground with a pestle to obtain a powder precursor, which was then placed in a tube furnace and pre-calcined at 300°C under the protection of an argon atmosphere, kept warm for 3 hours, then heated to 500°C at a rate of 5°C / min and calcined, kept warm for 10 hours, and finally cooled to room temperature in the tube furnace to obtain the borate-substituted sodium iron pyrophosphate positive electrode material Na4Fe3(PO4) 1.9 (BO3) 0.1 (P2O7).

[0057] Example 2

[0058] The preparation method of the borate-substituted modified sodium iron phosphate pyrophosphate positive electrode material of this embodiment is basically the same as that of Example 1, except that in step S2, the mass of ammonium dihydrogen phosphate is 0.454 g, the mass of boric acid is 0.0031 g, and the borate-substituted modified sodium iron phosphate pyrophosphate positive electrode material Na4Fe3(PO4) is 1.95 (BO3) 0.05 (P2O7).

[0059] Example 3

[0060] The preparation method of the borate-substituted modified sodium iron phosphate pyrophosphate positive electrode material of this embodiment is basically the same as that of Example 1, except that in step S2, the mass of ammonium dihydrogen phosphate is 0.443 g, the mass of boric acid is 0.0093 g, and the borate-substituted modified sodium iron phosphate pyrophosphate positive electrode material Na4Fe3(PO4) is 1.85 (BO3) 0.15 (P2O7).

[0061] Example 4

[0062] This embodiment provides a method for preparing a borate-substituted sodium iron pyrophosphate positive electrode material, comprising the following steps:

[0063] S1. Dissolve 0.3 g of polyvinyl pyrrolidone in 20 mL of deionized water and stir at room temperature for 30-50 min to obtain a clear solution. Weigh 1.212 g of ferric nitrate nonahydrate and add it to the above solution. Then weigh 0.345 g of oxalic acid and add it to the above solution. Stir continuously with a magnetic stirrer for 10 min to obtain a light green clear solution.

[0064] S2. 0.513 g of diammonium hydrogen phosphate and 0.424 g of sodium carbonate were added to the above solution in sequence, and the solution was stirred continuously with a magnetic stirrer for 10 to 20 min to obtain a clear light green aqueous solution of sodium iron pyrophosphate;

[0065] S3. Add 0.0382 g of sodium borate to the above solution and stir continuously with a magnetic stirrer for 10 to 30 min to obtain a clear solution;

[0066] S4. The above solution was transferred to an ultrasonic machine for ultrasonic treatment to fully and evenly mix to form an emerald green transparent solution;

[0067] S5. The emerald green transparent solution was transferred to a drying oven and dried at 140°C for 10 h to obtain a black xerogel;

[0068] S6. The obtained black dry gel was ground with a pestle to obtain a powder precursor, which was then placed in a tube furnace and pre-calcined at 400°C under the protection of an argon atmosphere, kept warm for 2 hours, then heated to 550°C at a rate of 5°C / min and kept warm for 8 hours. Finally, the tube furnace was cooled to room temperature to obtain the borate-substituted sodium iron pyrophosphate positive electrode material Na4Fe3(PO4). 1.9 (BO3) 0.1 (P2O7).

[0069] Comparative Example 1

[0070] A method for preparing a sodium iron phosphate pyrophosphate positive electrode material specifically comprises the following steps:

[0071] S1. Dissolve 0.3 g of polyvinyl pyrrolidone in 20 ml of deionized water and stir to obtain a clear solution. Weigh 0.834 g of ferrous sulfate heptahydrate and add it to the above solution. Then weigh 0.736 g of citric acid and add it to the above solution. Stir continuously for 10 min with a magnetic stirrer to obtain a light green clear solution.

[0072] S2. 0.460 g of diammonium dihydrogen phosphate and 0.544 g of sodium acetate were added to the above solution in sequence, and stirred continuously with a magnetic stirrer for 15 min to obtain a light green clear solution;

[0073] S3. The above solution was transferred to an ultrasonic machine to be fully and evenly mixed to form an emerald green transparent solution;

[0074] S4. The emerald green transparent solution was transferred to a drying oven and dried at 160°C for 10 h to obtain a black xerogel;

[0075] S5. The obtained black dry gel was ground with a pestle to obtain a powder precursor, which was then placed in a tubular furnace and pre-calcined at 300°C under the protection of an argon atmosphere, kept warm for 3 hours, then heated to 500°C at a rate of 5°C / min and calcined, kept warm for 10 hours, and finally cooled to room temperature in the tubular furnace to obtain the sodium iron pyrophosphate positive electrode material Na4Fe3(PO4)2(P2O7).

[0076] Figure 1 The XRD diagram of the positive electrode material of Examples 1 to 3 and Comparative Example 1. It can be seen from the XRD spectrum that the diffraction peaks are at 15.9°, 16.7°, 32.1°, 33.7° and 34.2°, corresponding to the (0 1 1), (2 1 0), (0 22), (2 2 2) and (6 0 2) planes of Na4Fe3(PO4)2(P2O7). Doping does not change the lattice structure of the original NFPP, so Examples 1 to 3 have the same crystal structure as Comparative Example 1, but it can be seen from the enlarged supplementary figure on the right that the main peaks of Examples 1, 2 and 3 are significantly shifted to the right compared to the undoped NFPP. Because boric acid has a smaller radius than phosphoric acid, partial replacement of the phosphate site will cause the XRD peak to shift to the right. The XRD results show that Na4Fe3(PO4) 1.9 (BO3) 0.1 (P2O7) cathode material has been successfully synthesized.

[0077] Figure 2 Na4Fe3(PO4) prepared in Example 1 1.9 (BO3) 0.1 (P2O7) SEM image of the positive electrode material. It can be seen from the image that the surface morphology is irregular granular. Figure 3 This is the SEM image of the Na4Fe3(PO4)2(P2O7) positive electrode material prepared in Comparative Example 1. It can be seen from the figure that the prepared Na4Fe3(PO4)2(P2O7) particles are agglomerated.

[0078] Application Examples

[0079] The positive electrode materials, conductive agent Super P, and polyvinylidene fluoride PVDF prepared in Examples 1 to 3 and Comparative Example 1 were mixed uniformly in a mass ratio of 7:2:1, dispersed in N-methyl-2-pyrrolidone NMP solvent to form a uniform slurry, and coated on aluminum foil using a scraper or a four-sided coater to form a positive electrode sheet. The coated aluminum foil was placed in a drying oven at 120°C and dried for 12 hours, and then the coated aluminum foil was cut into a circular electrode sheet with a diameter of 12 mm, and placed in a glove box to assemble into a button battery (CR2032). The prepared composite material was used as the working electrode, and a sodium block was used as the counter electrode to test its electrochemical performance, wherein the diaphragm used Whatman GF / A, the electrolyte system was a solute of 1M NaClO4 and a solvent formed by ethylene carbonate EC, dimethyl carbonate DMC and 5% fluoroethylene carbonate FEC, and the volume ratio of EC and DMC was 1:1.

[0080] The assembled button battery was subjected to electrochemical performance test. The test instrument used for the electrochemical performance test was as follows: LANHE-CT2001A multi-channel battery test system produced by Wuhan Landian Electronics Co., Ltd., with a static time of 12 h, a voltage window range of 1.8-4.2 V, and a current density range of 5000 mA g -1 , the number of cycles ranges from 150 to 10,000 times.

[0081] Figure 4 Na4Fe3(PO4) prepared in Example 1 1.9 (BO3) 0.1 The charge and discharge curves of the first three cycles of the charge and discharge process of the (P2O7) positive electrode material show that there are three voltage platforms corresponding to charging and discharging respectively, and the cycle stability is excellent.

[0082] Figure 5 Na4Fe3(PO4) prepared in Example 1 1.9 (BO3) 0.1 The cycling performance diagram of the (P2O7) positive electrode material at a current density of 0.2A / g. It can be seen from the figure that the positive electrode material still maintains a specific capacity of up to 115 mAh / g after 150 cycles, showing good cycling stability.

[0083] Figure 6 Na4Fe3(PO4) prepared in Example 2 1.95 (BO3) 0.05 Cycling performance diagram of (P2O7) positive electrode material at current density of 0.2A / g.

[0084] Figure 7 Na4Fe3(PO4) prepared in Example 3 1.85 (BO3)0.15 (P2O7) Cyclic performance diagram of positive electrode material at a current density of 0.2A / g;

[0085] Figure 8 This is the cycling performance diagram of the Na4Fe3(PO4)2(P2O7) positive electrode material prepared in Comparative Example 1 at a current density of 0.2A / g.

[0086] The cycle performance of the positive electrode materials prepared in Examples 1 to 3 and Comparative Example 1 at a current density of 0.2 A / g is shown in Table 1.

[0087] Table 1 Cyclic performance at a current density of 0.2 A / g

[0088] By comparing the data of Example 1 and Comparative Example 1, it can be seen that the doping of borate anion groups can improve the initial specific capacity and cycle stability of the sodium iron phosphate pyrophosphate positive electrode material. By comparing Examples 1 to 3, it can be found that too much or too little amount of doped borate anions will reduce the initial specific capacity and cycle stability of the sodium iron phosphate pyrophosphate positive electrode material. The increase in the amount of borate anions doped in Example 3 will also reduce the initial specific capacity and cycle stability of the sodium iron phosphate pyrophosphate positive electrode material, indicating that excessive doping may cause structural damage during the cycle, problems such as active material shedding, and lead to a decrease in the cycle. Therefore, the doping of an appropriate proportion of borate anion groups can improve the initial specific capacity and cycle stability of the sodium iron phosphate pyrophosphate positive electrode material.

[0089] Fig. 9 Na4Fe3(PO4) prepared in Example 1 1.9 (BO3) 0.1 (P2O7) positive electrode material, Na4Fe3(PO4) prepared in Example 2 1.95 (BO3) 0.05 (P2O7) positive electrode material, Na4Fe3(PO4) prepared in Example 3 1.85 (BO3) 0.15 The rate diagram of the positive electrode material of Example 1 and the positive electrode material of Na4Fe3(PO4)2(P2O7) prepared in Comparative Example 1. As can be seen from the figure, the positive electrode material of Example 1 has the highest discharge capacity retention rate at different rates, showing excellent rate performance.

[0090] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a borate-substituted sodium iron pyrophosphate positive electrode material, characterized in that: The following steps are involved: S1. A boron source is added to an aqueous solution of sodium iron pyrophosphate, mixed evenly to obtain a first solution, and dried to obtain a dry gel; S2. Under the protection of an inert gas, the dry gel is calcined to replace part of the phosphate with borate to obtain a borate-substituted modified sodium iron pyrophosphate positive electrode material.

2. The method for preparing the borate-substituted sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The molar ratio of the sodium ferric pyrophosphate to the boron source is 1:(0.05-0.15).

3. The method for preparing the borate-substituted modified sodium iron pyrophosphate positive electrode material according to claim 2, characterized in that: The molar ratio of the sodium ferric pyrophosphate to the boron source is 1:(0.05-0.1).

4. The method for preparing the borate-substituted modified sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The boron source includes at least one of boric acid, sodium borate and calcium borate.

5. The method for preparing the borate-substituted modified sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The calcination temperature is 500-550° C., and the calcination time is 6-10 hours.

6. The method for preparing the borate-substituted modified sodium iron pyrophosphate positive electrode material according to claim 1, characterized in that: The preparation method of the sodium ferric phosphate pyrophosphate aqueous solution is as follows: polyvinyl pyrrolidone, an iron source and a carbon source are dissolved in water, and stirred evenly to obtain a second solution; a phosphorus source and a sodium source are added to the second solution, and stirred evenly to obtain the sodium ferric phosphate pyrophosphate aqueous solution.

7. The method for preparing the borate-substituted sodium iron pyrophosphate positive electrode material according to claim 6, characterized in that: The molar ratio of the iron source to the carbon source is 1:(3-4.5); And / or, the molar ratio of the sodium source to the phosphorus source is 1:(0.8-1); And / or, the molar ratio of the iron source to the phosphorus source is 3:(3.8-3.95).

8. The method for preparing the borate-substituted modified sodium iron pyrophosphate positive electrode material according to claim 6, characterized in that: The iron source includes at least one of ferrous sulfate heptahydrate, ferric nitrate nonahydrate, and ferrous oxalate; And / or, the carbon source comprises at least one of citric acid, oxalic acid and glucose; And / or, the phosphorus source includes at least one of diammonium phosphate, diammonium hydrogen phosphate, and sodium dihydrogen phosphate dihydrate; And / or, the sodium source includes at least one of sodium dihydrogen phosphate dihydrate, sodium acetate, sodium carbonate, and sodium nitrate.

9. The borate-substituted sodium iron pyrophosphate positive electrode material prepared by the method according to any one of claims 1 to 8.

10. Use of the borate-substituted sodium iron phosphate pyrophosphate positive electrode material prepared by the method according to any one of claims 1 to 8 in a sodium ion battery.

Citation Information

Patent Citations

  • Preparation method of phosphate potential boron-doped carbon-wrapped phosphoric acid iron-lithium material

    CN103219516A

  • Positive electrode material for sodium-ion battery and preparation method thereof

    CN108046231A

  • Preparation method for porous carbon modified ferric sodium pyrophosphate / carbon positive electrode material of sodium ion battery

    CN113104828A

  • Positive electrode active material, preparation method thereof, positive electrode plate, battery and electric equipment

    CN117038973A

  • Hierarchical porous sodium ion battery positive electrode material and preparation method and application thereof

    CN118117076A

Cited By

  • Complex-phase ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

    CN119812290A

  • NFPP-based positive electrode material, preparation method thereof and sodium ion battery

    CN121748339A